A Pathogenic Missense Variant in NFKB1 Causes Common Variable Immunodeficiency Due to Detrimental Protein Damage - Fliegauf, Manfred; Krüger, Renate; Steiner, Sophie; Hanitsch, Leif Gunnar; Büchel, Sarah; Wahn, Volker; von Bernuth, Horst; Grimbacher, Bodo (Frontiers in Immunology, 2021)
In common variable immunodeficiency (CVID), heterozygous damaging NFKB1 variants represent the most frequent monogenic cause. NFKB1 encodes the precursor p105, which undergoes proteasomal processing to generate the mature NF-κB transcription factor subunit p50. The majority of NFKB1 sequence changes comprises missense variants of uncertain significance (VUS), each requiring functional evaluation to assess causality, particularly in families with multiple affected members presenting with different phenotypes. In four affected members of a German family, all diagnosed with CVID, we identified a previously uncharacterized heterozygous NFKB1 missense variant (c.1049A>G; p.Tyr350Cys). The clinical phenotypes varied markedly regarding onset, frequency and severity of infections. Consistent immunologic findings were hypogammaglobulinemia with normal specific antibody response to protein- and polysaccharide-based vaccinations, reduced switched memory B cells and decreased lymphocyte proliferation upon stimulation with the B cell mitogen SAC. To assess the pathogenicity of the NFKB1 missense variant, we employed immunophenotyping and functional analyses in a routine in vitro cell culture model. Following site-directed mutagenesis to introduce the variant into overexpression vectors encoding EGFP-fused p105 or p50, we analyzed transiently transfected HEK293T cells by confocal imaging and Western blotting. The cytoplasmic p105-Tyr350Cys precursor gained only weak expression levels indicating accelerated decay. The missense change disabled processing of the precursor to prevent the generation of mutant p50. Unlike the wildtype p50, the overexpressed mutant p50-Tyr350Cys was also not sustainable and showed a conspicuous subnuclear mislocalization with accumulation in dense aggregates instead of a homogenous distribution. Electrophoretic mobility shift assays, fluorescence-based reporter gene analyses and co-transfection experiments however demonstrated, that the DNA binding activity of p50-Tyr350Cys and the interaction with RelA(p65), IB and wildtype p50 were preserved. Mutation carriers had reduced p105 and p50 levels, indicating insufficient protein amounts as the most likely primary defect. In conclusion, the missense variant c.1049A>G caused a detrimental defect, preventing the persistent expression of both, the p105-Tyr350Cys precursor and the mature p50-Tyr350Cys. The variable clinical phenotypes among affected family members sharing an identical pathogenic NFKB1 variant supports a disease mechanism provoked by a p105/p50 (haplo)insufficient condition.